The Use of ChatGPT in Teaching Writing - Haekal Fikri; Nurdin Noni; La Sunra (International Journal of Language, Education, and Literature, 2024)
This study aims to determine (1) the implementation of ChatGPT in teaching writing and (2) the teacher and students' perceptions of ChatGPT in teaching writing. This study used qualitative descriptive methodology. This study also used purposive sampling with eight participants: one teacher and seven students in the XI grade majoring in visual communication design at SMKN 1 Polewali. The data collection instruments used in this study were observation and interviews. The data validity checking technique used triangulation. The data analysis techniques are carried out in several stages: collection, reduction, display, and conclusion. The findings of this study revealed that ChatGPT has been well implemented in teaching writing. This is because the teacher prepared a lesson plan incorporating ChatGPT, used ChatGPT as a feedback provider in the learning process, and assessed students' writing skills. Researchers also revealed both the teacher and students highly perceived the ease of use of ChatGPT in teaching writing. This is because ChatGPT is easy to learn, easy to control, easy to use, clear, easy to understand, flexible, and easy to become skillful. Furthermore, this study revealed both the teacher and students highly perceived the usefulness of ChatGPT in teaching writing. This aligns with ChatGPT's capability to accelerate work, improve performance, increase effectiveness, simplify work, and provide utility.